Field Survey Findings of Flood Impacts and Resilience of Electrical Systems in Nepalese Hydropower Plants - Sah, Raju; Gautam, Nikil; Pokharel, Aavas; Gautam, Basanta Kumar; Silwal, Bishal (Journal of Science and Engineering, 2025)
Nepal’s dependence on hydropower highlights the critical importance of ensuring the resilience of hydropower infrastructure amid increasing climate-induced disasters. This study investigates the impacts of flood events on the structural and electrical integrity of three types of hydropower plants in Nepal—run-of-river (RoR), peaking run-of-river (PRoR), and reservoir-based systems. Field observations were conducted at Trishuli, Kulekhani-I, and Mandu hydropower plants to assess flood-induced damage, system downtime, and operational vulnerabilities. Key aspects such as sediment accumulation, mechanical wear, switchyard exposure, and emergency response protocols were analyzed to understand each plant’s capacity to withstand and recover from flood events. The findings reveal significant disparities in resilience based on plant design and location, with RoR plants demonstrating higher susceptibility to direct flood impacts. This study highlights the urgent need for improved flood forecasting, infrastructure upgrades, and adaptive operational strategies to bolster the long-term sustainability and reliability of Nepal’s hydropower sector.